Penggunaan Bahasa Asing dalam Konteks Pendidikan Bahasa di Indonesia: Beberapa Isu Sentral - Suwartono suwartono (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2007)
This paper presents issues on foreign language use in the context of language education in Indonesia. Some people believe that our â€œoldâ€ language(s) would only hinder the acquisition of a â€œnewâ€ one. Whatever the reason it is wrong to leave the language(s) we have already acquired in attempt to acquire a new one. Even, in the case of our national language, Indonesian, we have to preserve it, develop it and, when possible, upgrade its position among the important languages of the world. One way is by using it properly for communication while learning another (foreign) language. Just as any other skills acquisition, the key to success in a foreign language learning is practice. Since foreign language learning environment is in general not conducive to have automatic practices, hard, deliberate efforts are frequently required for compensation. Unfortunately, only few learners do this. Therefore, our discussion is centered around learner strategies. In relation with this, foreign language teacher professionalism is crucial. Classroom activities he/she develops should be able to create setting for target language intensive use and build learner autonomy â€“ a condition scarcely observed in our language classrooms.